Supplementation with milk fat globule membrane from early life reduces maternal separation-induced visceral pain independent of enteric nervous system or intestinal permeability changes in the rat. (1st June 2022) - Collins, James M.; Caputi, Valentina; Manurung, Sarmauli; Gross, Gabriele; Fitzgerald, Patrick; Golubeva, Anna V.; Popov, Jelena; Deady, Clara; Dinan, Timothy G.; Cryan, John F.; O'Mahony, Siobhain M.
Abstract: Nutritional approaches have emerged over the past number of years as suitable interventions to ameliorate the enduring effects of early life stress. Maternal separation (MS) is a rodent model of early life stress which induces widespread changes across the microbiota-gut-brain axis. Milk fat globule membrane (MFGM) is a neuroactive membrane structure that surrounds milk fat globules in breast milk and has been shown to have positive health effects in infants, yet mechanisms behind this are not fully known. Here, we investigated the effects of MFGM supplementation from birth on a variety of gut-brain signalling pathways in MS and non-separated control animals across the lifespan. Specifically, visceral sensitivity as well as spatial and recognition memory were assessed in adulthood, while gut barrier permeability, enteric nervous system (ENS) and glial network structure were evaluated in both early life and adulthood. MS resulted in visceral hypersensitivity, which was ameliorated to a greater extent by supplementation with MFGM from birth. Modest effects of both MS and dietary supplementation were noted on spatial memory. No effects of MS were observed on enteric neuronal or glial networks in early life or adulthood, however an increase in the immunoreactivity of βIII-tubulin in adult colonic myenteric ganglia was noted in the MFGM intervention non-separated group. In conclusion, dietary supplementation with MFGM from birth is sufficient to block MS-induced visceral hypersensitivity, highlighting its potential value in visceral pain-associated disorders, but future studies are required to fully elucidate the mechanistic role of this supplementation on MS-induced visceral pain. This article is part of the Special Issue on 'Advances in mechanisms and therapeutic targets relevant to pain'. Highlights: Early life stress results in changes in behaviour and visceral sensation. Milk fat globule membrane administered from birth throughout the lifespan. Early life stress-induced visceral pain was reversed by milk fat globule membrane. Milk fat globule membrane acts independently of enteric nervous system.